Novel repumping on 3P0→3D1 for Sr magneto-optical trap and Landé g factor measurement of 3D1. (23rd October 2020) - Zhang, Shengnan; Ramchurn, Preetam; Menchetti, Marco; Ubaid, Qasim; Jones, Jonathan; Bongs, Kai; Singh, Yeshpal
Abstract: We realize an experimental facility for cooling and trapping strontium (Sr) atoms and measure the Landé g factor of 3 D1 of 88 Sr. Thanks to a novel repumping scheme with the 3 P2 → 3 S1 and 3 P0 → 3 D1 combination and the permanent magnets based self-assembled Zeeman slower, the peak atom number in the continuously repumped blue magneto-optical trap is enhanced by a factor of 15 with respect to the non-repumping case, and reaches ∼1 billion. Furthermore, using the resolved-sideband Zeeman spectroscopy, the Landé g factor of 3 D1 is measured to be 0.4995(88) showing a good agreement with the theoretical value of 0.4988. The results will have an impact on various applications including atom laser, dipolar interactions, quantum information and precision measurements.